A mutation modulating DDX3Y gene expression cosegregates with the major Y‐chromosomal haplogroups and with testis size in Hu sheep. (28th December 2021) - Zhang, Xueying; Liao, Zhi; Tang, Shijie; Yuan, Zehu; Li, Fadi; Yue, Xiangpeng
Summary: Variations in the Y‐chromosome are usually correlated with male‐specific traits. However, this condition has been described only sporadically, even in human genetics. The present study was conducted to clone the full‐length gene sequence of ovine DEAD ‐ box helicase 3, Y ‐ linked ( DDX3Y ), and investigate the effect of the expression and variation of DDX3Y on the reproductive traits of Hu sheep. Consequently, we identified the full coding sequence and genomic sequence of ovine DDX3Y . Quantitative PCR (qPCR) analysis showed that ovine DDX3Y was highly expressed in testis, and the expression level increased during testicular development. Furthermore, individuals with larger testis at 6 months expressed significantly more DDX3Y mRNA in the testis than individuals with smaller testis. Notably, a novel SNP (g. 12657 C>A) in the 3′ untranslated region was identified in Hu sheep and Tan sheep according to the investigation of the full DDX3Y genomic sequence of 1069 individuals from nine sheep breeds. Association analysis revealed that the SNP was significantly related to testis size in Hu sheep. Meanwhile, Hu rams with the derived C allele showed significantly higher expression levels of DDX3Y in testis than those with the ancestral A allele. In addition, data mining in a previous study showed that the C allele cosegregated with the globally major Y‐chromosomal haplogroups y‐HA and y‐HC, and the A allele is found in all rams with haplogroups y‐HB1, y‐HB2 and y‐HD. This study suggests that the association of the Y‐chromosomal haplogroups with testis size in Hu sheep can be extrapolated to the sheep population worldwide.